INFLUENCE OF KNOWLEDGE ON SEXUAL EDUCATION AND REPRODUCTIVE HEALTH IN SECONDARY EDUCATION LIMA, PERÚ - Sotomayor-Garnica, María (2023)
The present study was carried out in order to diagnose the level of knowledge about sexuality and reproductive health in secondary education teachers and its influence on the level of information in students of the Educational Institution Nuestra Señora de Guadalupe, Lima, Perú, of a quantitative nature with a hypothetical deductive approach, of applied type, causal-explanatory correlational of cross-sectional design, the technique used was the survey, with two questionnaires. The surveys were conducted during 2019 with 15 teachers who teach the course on personal development, citizenship and civics, then the questionnaire was applied to 243 students in the 3rd, 4th, and 5th year of secondary school about Knowledge of sexual education and reproductive health. Conclusion according to the results obtained that the students have a low level of information about sexuality and reproductive health, sexual experience, and protection. Regarding teachers, the results show that reinforcement is required in issues about human sexuality regarding relationships and knowledge of sexual practices, effective educational strategies, and care of the body, and they have an influence on the information they provide to students. It is recommended that the teacher, in addition to their knowledge and professional updating in the subject involved, must have the personal skills to deal with the contents with fluency and spontaneity proposed in the program, free of limitations on the subject of sexuality. Keywords: Knowledge – Human sexuality – Protection – Reproductive health – Sex education – Sexuality